Financial Management Practices of Mosques in Indonesia: Is Self-Control Important for Moderation? - Habibi, Ahmad; Syarif, Ahmad Hazas; Normasyhuri, Khavid; Nurmalia, Gustika (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2023)
Abstract. This study aims to optimize the allocation of financial resources for religious institutions in Indonesia, focusing on Lampung Province context. The quantitative methods with Smart PLS fi.0 examine the relationship between financial knowledge, financial attitudes, and the influence of self-control on financial management. This aims to determine whether self-control can improve or hinder financial management. 500 respondents were selected randomly. Those who are involved as administrators of religious organizations in mosques in Lampung. Data was collected using a Google form and using a Likert Scale. Research findings show a positive relationship between financial knowledge, financial attitudes, and financial management. Self-control can improve the relationship between financial knowledge and financial attitudes towards the financial management of religious institutions. Furthermore, self-control can improve the relationship between financial knowledge and financial attitudes in the financial administration of religious institutions. Abstrak. Penelitian ini bertujuan untuk mengoptimalkan alokasi sumber daya keuangan bagi lembaga keagamaan di Indonesia, dengan fokus pada konteks Provinsi Lampung. Metode kuantitatif dengan Smart PLS fi.0 digunakan untuk menguji hubungan pengetahuan keuangan, sikap keuangan, dan pengaruh pengendalian diri terhadap pengelolaan keuangan. Hal ini bertujuan untuk mengetahui apakah pengendalian diri dapat meningkatkan atau menghambat pengelolaan keuangan. 500 responden dipilih secara acak. Responden adalah orang yang terlibat sebagai pengurus organisasi keagamaan di masjid-masjid di Lampung. Data dikumpulkan dengan menggunakan Google form dan menggunakan Skala Likert. Temuan penelitian menunjukkan adanya hubungan positif antara pengetahuan keuangan,sikap keuangan, dan pengelolaan keuangan. Pengendalian diri dapat meningkatkan hubungan antara pengetahuan keuangan dan sikap keuangan terhadap pengelolaan keuangan lembaga keagamaan. Selanjutnya pengendalian diri dapat meningkatkan hubungan antara pengetahuan keuangan dan sikap keuangan dalam pengelolaan keuangan lembaga keagamaan.